ABORTUS DALAM PANDANGAN HUKUM ISLAM - Alwi, Zulfahmi (Institut Agama Islam Negeri (IAIN) Palu, 2013)
Abstract. Generally, abortion done in case of unwanted pregnancy and was usually motivated by a variety of factors, including economic, social, contraceptive failure in married couples, as well as sex of unmarriad couples. Islam strictly prohibits the act of abortion with social and economic motives. Abortion has absolutely forbidden unless itâs motivation based on justifiable reason in Islam. Perpetrators of abortion may be punished by heavy penalty, which is to pay al-ghurrah or freeing slave. If the penalty of al-ghurrah is applied in contemporary life, the content of the sentence is determined by a court verdict.Â Islam greatly appreciates human existence since the early stages of events. Every effort to obstruct the growth of the fetus or to remove it from the womb before the arrival time of the birth naturally can not be tolerated.Kata kunci: aborsi, al-ghurrah, janin, ruh, hukum Islam.